The indicators of decent work in the corporate environment of women in the civil police of the state of Rio Grande do Sul. - Madruga, Sergio Rossi; Arigony, Marcelo Mendes; Madruga, Lucia Rejane da Rosa Gama (Revista de Administração da UFSM, 2018)
This study deals with the work of women in the Civil Police of the State of Rio Grande do Sul, under the decent work criteria of the International Labor Organization. The research is classified in the field of sustainability, in the social aspect, related to corporate social responsibility. The aim was to analyze the women’s environment, based on the decent work criteria. The data collection was performed from several sources of evidence, making use of primary and secondary data. The study has a qualitative nature, based on an observation script and a flexible instrument composed of open questions. An interpretation for the use of a content analysis procedure. Women began to work from the 1970s onwards and occupy a prominent place, on par with men, despite some evidence of limited opportunities. The general perception is to disagree with the ILO’s indicators, with the exception of criteria related to security and social dialogue, as well as stability and incomes, which are fully or partially met. However, there is no adequacy of work for ILO workers, especially for safety, equality, opportunities, conciliation and working hours.